2022
DOI: 10.1177/10499091221089337
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Concurrent Hospice Care: Cost Implications of a Hybrid Payment Model

Abstract: Background: Implementation of concurrent hospice care led to a new hybrid payment model that combines hospice payments with payments for non-hospice medical care. Little is known about the cost implications of this new hybrid payment model. Objective: The purpose was to identify costs and compare concurrent care and standard hospice care costs by estimating the average incremental Medicaid cost of care over time. Methods: Using national Medicaid data of 18 147 hospice children and a multilevel generalized line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…For hospice stays of 15 days or more, this study showed that enrollment in concurrent care was associated with a significant increase in Medicaid costs compared to standard hospice care in Appalachia. This result mirrors findings from the previous study 26 . However, the current report also found that although the unadjusted Medicaid costs of concurrent care were higher in rural areas than in urban when controlled for patients' demographic and health conditions, the costs were lesser in rural areas than in urban.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…For hospice stays of 15 days or more, this study showed that enrollment in concurrent care was associated with a significant increase in Medicaid costs compared to standard hospice care in Appalachia. This result mirrors findings from the previous study 26 . However, the current report also found that although the unadjusted Medicaid costs of concurrent care were higher in rural areas than in urban when controlled for patients' demographic and health conditions, the costs were lesser in rural areas than in urban.…”
Section: Discussionsupporting
confidence: 87%
“…LOS measured the total number of days enrolled in hospice care. It was stratified into 3 time intervals: 1 day, 2‐14 days, and 15 days or more 26 …”
Section: Methodsmentioning
confidence: 99%
“…23 However, there is an interesting and unique cost profile that emerges based on the number of days children are enrolled in hospice care. 23 Compared with standard hospice care, children receiving concurrent care had significantly lower total costs and inpatient costs with a hospice length of stay of 14 days or less. At a length of hospice stay of 15 days or more, concurrent care demonstrated significantly higher costs across all measures: total costs, inpatient costs, outpatient costs, and prescription costs.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…It considers the costs concerning the clinical benefits by comparing 1 service (eg, concurrent hospice care) to another service (eg, standard hospice care) 15 . By definition, the costs (eg, total costs, inpatient costs, outpatient costs, prescription costs) of concurrent hospice care will be higher than standard hospice care because in standard hospice care, patients waive any medical care services 23 . However, there is an interesting and unique cost profile that emerges based on the number of days children are enrolled in hospice care 23 .…”
Section: Conceptual Modelmentioning
confidence: 99%
See 1 more Smart Citation